Analisis Kebutuhan Pengembangan E-Modul Perubahan Iklim dan Pemanasan Global Terintegrasi Model Project Based Learning (PjBL) - Novita, Novita; Sari, Silvi Yulia (Lembaga Yasin AlSys, 2023)
This study aimed to assess the significance of creating a comprehensive electronic module on project-based learning (PjBL) focused on climate change and global warming. As a result, an initial investigation was undertaken within this research, comprising a review of existing literature and on-site data collection. The research carried out was a type of qualitative descriptive research. Research data was obtained from analyzing teacher needs through interviews and analyzing student needs through filling out questionnaires. The PjBL integrated e-module developed consists of text, images, videos, interactive quizzes, and assignment collection templates via g-form. The development of e-modules is aimed at supporting students to learn independently. During its creation, the e-module made use of the Flip PDF Professional software application. A requirement assessment was conducted to gather insights about the physics learning procedure, the utilization of instructional resources in physics education, and the requisites of students and educators for educational materials (e-modules). From the needs analysis of 51 classes, As many as 80% of students felt that the teacher's explanation alone was not enough. Apart from that, 86% of students need a long time to understand the material on climate change and global warming. Thus, it is necessary to develop an integrated PjBL e-module on climate change and global warming material.